Influence of metabolites on protein binding of verapamil enantiomers. - Johnson, J A (1995)
This study investigated the effect of verapamil metabolites on R- and S-verapamil protein binding in plasma samples collected from subjects prior to rac-verapamil dosing and following single dose and steady state rac-verapamil dosing. In vitro studies of the effects of norverapamil, D617 and D620 on R- and S-verapamil protein binding were also performed. Protein binding of R- and S-verapamil was unchanged following single and multiple doses of rac-verapamil as compared with protein binding in pre-dose samples. In vitro, norverapamil had no effect on R- and S-verapamil protein binding up to 1000 ng ml-1. Norverapamil 5000 ng ml-1 caused a 30% increase in free fraction of both R- and S-verapamil. D617 and D620 concentrations up to 5000 ng ml-1 had no effect on R- and S-verapamil protein binding. We conclude the metabolites of verapamil have no clinically significant effect on R- and S-verapamil protein binding.